Meta-analysis of epigenome-wide association studies of carotid intima-media thickness - Portilla-Fernández Eliana; Hwang Shih-Jen; Wilson Rory; Maddock Jane; Hill W. David; Teumer Alexander; Mishra Pashupati P.; Brody Jennifer A.; Joehanes Roby; Ligthart Symen; Ghanbari Mohsen; Kavousi Maryam; et al. (SPRINGER, 2022)
Common carotid intima-media thickness (cIMT) is an index of subclinical atherosclerosis that is associated with ischemic stroke and coronary artery disease (CAD). We undertook a cross-sectional epigenome-wide association study (EWAS) of measures of cIMT in 6400 individuals. Mendelian randomization analysis was applied to investigate the potential causal role of DNA methylation in the link between atherosclerotic cardiovascular risk factors and cIMT or clinical cardiovascular disease. The CpG site cg05575921 was associated with cIMT (beta = −0.0264, p value = 3.5 × 10–8) in the discovery panel and was replicated in replication panel (beta = −0.07, p value = 0.005). This CpG is located at chr5:81649347 in the intron 3 of the aryl hydrocarbon receptor repressor gene (AHRR). Our results indicate that DNA methylation at cg05575921 might be in the pathway between smoking, cIMT and stroke. Moreover, in a region-based analysis, 34 differentially methylated regions (DMRs) were identified of which a DMR upstream of ALOX12 showed the strongest association with cIMT (p value = 1.4 × 10–13). In conclusion, our study suggests that DNA methylation may play a role in the link between cardiovascular risk factors, cIMT and clinical cardiovascular disease.